A comparative and retrospective study on the efficacy of caudal epidural steroid injection plus ganglion impar block versus ganglion impar block in patients with coccydynia (Annals of Medical Research, 2022)
Aim: Coccydynia is defined as pain in the area of the coccyx. The initial treatment is conservative therapy, although several interventional treatments can be performed in patients who do not respond well. The purpose of this study is to evaluate the efficacies of ganglion impar blocks and caudal epidural steroid injections in the treatment of coccydynia.Materials and Methods: From January 2019 to June 2021, a retrospective review was conducted on 65 patients who underwent ganglion impar block (n = 25) or ganglion impar block and caudal epidural steroid injection (n = 40) for coccydynia. Pain scores at baseline and at the first and third months after the procedure were compared between two groups. Results: In both groups, a statistically significant decrease was found at the first and third months when post-injection Visual Analog Scale (VAS) scores were compared to the basal VAS scores (p < 0.05). However, no statistically significant difference was found between the groups at the first and third months (p = 0.39 and p = 0.82, respectively).Conclusion: Ganglion impar block is effective for patients with coccydynia in providing pain relief. However, the addition of caudal epidural steroid injection to the ganglion impar block in patients with coccydynia has no additional contribution to pain relief.
Keywords: Coccydynia; Ganglion impar block; Caudal epidural; Coccydynia treatment